Evaluating the Effectiveness of an Integrated Prehospital and Post-Discharge Care Model Combining EMS and Rehabilitation Services on Improving Functional Outcomes and Quality of Life among Stroke Patients in Hafr Al-Batin: A Systematic Review - Mohammed Awadh Jawan Alshammari; Nawaf Dasan R Aldhafeeri; Mahli Mutlaq Mahli Alrashed; Khaled Safaq Al-Harbi; Mofareh Muflih A Alrashed; Ayed Hamed A Alonquodi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Stroke is a leading cause of disability and mortality worldwide, requiring prompt and coordinated care across the continuum of healthcare services. Integrated care models combining prehospital and post-discharge services have demonstrated promising results in improving outcomes for stroke patients. This systematic review aims to evaluate the effectiveness of an integrated prehospital and post-discharge care model that combines emergency medical services (EMS) and rehabilitation services on enhancing functional outcomes and quality of life among stroke patients in Hafr Al-Batin, Saudi Arabia. A comprehensive literature search will be conducted using pertinent databases, and studies will be selected based on pre-defined inclusion and exclusion criteria. The quality of the included studies will be assessed using standardized tools, and the data will be extracted and synthesized using a narrative approach. The findings will provide evidence regarding the effectiveness and feasibility of integrated stroke care models in the Saudi Arabian context and inform the development and implementation of similar models in other settings. The review will also identify the gaps and challenges in the current evidence and provide recommendations for future research and practice.